PENGARUH KUALITAS KEHIDUPAN KERJA DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PERAWAT RSUD PETALA BUMI PROVINSI RIAU - Sari, Yosi Fatmala; ", Kasmirudin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine how the influence of quality of work life and work motivation to job satisfaction nurse RSUD Petala Bumi Riau Province. The method of this research is descriptive and quantitative using SPSS 21 program, where the sample used is non-civil servants with respondents 48 people. For sampling technique used census method. Data collection techniques through questionnaires, observations and interviews. The result of analysis using validity test, reliability test, test of determination, simple linear regression test, multiple linear regression test, t test and F test so that it can be seen that the variable of quality of work life have a significant effect on nurse job satisfaction, that work motivation significantly influence job satisfaction nurse, and have a significant effect between quality of work life and work motivation to nurse job satisfaction. Keywords: quality of work life, work motivation, and job satisfaction